Using Waiting Queue Models to Study Reducing the Phenomenon of Delay in One of the Health Institutions in Baghdad - Jasaim, Saleemah H.; Abbas, Iraq T. (Iraqi Journal of Science, 2025)
The research presents a proposed model for the role of using waiting queue models in improving the performance of health institutions in Iraq, Baghdad. The proposed model relies on a set of numerical methods, the most important of which is the quantitative programming method (QM for Windows). The model analyzes the stability of the system and simulations are performed to evaluate its performance. The main goal of this paper is to improve the performance of these government medical institutions in Iraq in a scientifically sound manner, so that the proposed model is applied to reduce crowding and waiting in health centers. This study was applied in one of the health centers in Baghdad, Palestine Street (Al-Idrisi neighborhood) during the period extending from 1/3/2019 to 3/1/2019. The study concluded by presenting an alternative model to improve the current situation in the institution under study, as this contributed the alternative is to improve all performance indicators. Other models can be evaluated using artificial intelligence, which enables us to enhance the system and improve prediction accuracy in different health center scenarios.